Genome mining for the discovery of new nitrilases in filamentous fungi - Kaplan, Ondřej; Bezouška, Karel; Malandra, Anna; Veselá, Alicja B; Petříčková, Alena; Felsberg, Jürgen; Rinágelová, Anna; Křen, Vladimír; Martínková, Ludmila (Biotechnology letters, 2011)
our aim is to describe new fungal nitrilases whose sequences were published but whose catalytic properties were unknown. We adapted for expression in E. coli three of the genes and confirmed that the enzymes acted on organic nitriles. The genome mining approach was used to search for nitrilases in filamentous fungi. Synthetic genes encoding nitrilases in Aspergillus niger, Gibberella moniliformis and Neurospora crassa were expressed in Escherichia coli. This is the first heterologous expression of fungal enzymes of this type. The recombinant enzyme derived from G. moniliformis was an aromatic nitrilase with an activity of 390 U l(-1) culture with benzonitrile as substrate. This was much less than the activities of the recombinant enzymes derived from A. niger and N. crassa that had activities of 2500 and 2700 U l(-1) culture, respectively, with phenylacetonitrile as substrate.
Keywords: exprese genu; aminohydrolasy; Gene Expression; fungální proteiny; Neurospora crassa; klonování DNA; Escherichia coli; Aminohydrolases; Recombinant Proteins; Aspergillus niger; výpočetní biologie; nitrily; rekombinantní proteiny; Computational Biology; Genome, Fungal; organické látky; Organic Chemicals; genom fungální; Cloning, Molecular; Gibberella; Nitriles; Fungal Proteins